2012
DOI: 10.1002/jbio.201200075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of carbapenem‐resistant Acinetobacter baumannii clones using infrared spectroscopy

Abstract: In this work we assessed the discriminatory ability of Fourier‐transform Infrared Spectroscopy (FTIR) in 22 representative isolates from a collection of 318 carbapenem‐hydrolyzing class D β ‐lactamases (CHDL)‐producing Acinetobacter spp. (5 hospitals; 2001–2008) previously characterized by DNA‐based typing methods. FTIR spectra were acquired with a Bruker spectrometer and analyzed with support of several chemometric tools. The results showed that FTIR spectroscopy was able to distinguish the main CHDL‐producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…FTIRS and MALDI-TOF MS demonstrated a similar potential for the discrimination of two pathovars of X. oryzae [79] and Goodacre et al [91] concluded that FTIRS was better than pyrolysis mass spectrometry and dispersive Raman microscopy for the species discrimination of 59 Gram-positive and -negative bacteria. Regarding the subspecies level, the discrimination of an Acinetobacter collection belonging to four distinct sequence types [69,70,89] was better with FTIRS than MALDI-TOF MS in. In contrast, similar results were obtained with FTIRS and MALDI-TOF MS regarding the discrimination of Klebsiella oxytoca [87] and Campylobacter strains.…”
Section: Competing Spectroscopic Techniquesmentioning
confidence: 94%
See 3 more Smart Citations
“…FTIRS and MALDI-TOF MS demonstrated a similar potential for the discrimination of two pathovars of X. oryzae [79] and Goodacre et al [91] concluded that FTIRS was better than pyrolysis mass spectrometry and dispersive Raman microscopy for the species discrimination of 59 Gram-positive and -negative bacteria. Regarding the subspecies level, the discrimination of an Acinetobacter collection belonging to four distinct sequence types [69,70,89] was better with FTIRS than MALDI-TOF MS in. In contrast, similar results were obtained with FTIRS and MALDI-TOF MS regarding the discrimination of Klebsiella oxytoca [87] and Campylobacter strains.…”
Section: Competing Spectroscopic Techniquesmentioning
confidence: 94%
“…Species FTIRS -- [41] (Continued) Rathayibacter tritici Species FTIRS -- [41] Lactococcus cremoris Species FTIRS PLS, KPLS [42] Rhodococcus erythropolis Species FTIRS -- [38] Acinetobacter spp. Species FTIRS, FTIRS-ATR HCA, PCA, DFA, ANN [43][44][45] Acinetobacter baumannii Sequence type FTIRS-ATR PLSDA [69,70] Burkholderia cepacia complex Species FTIRS PLS, PCA, SIMCA, ANN [45,46] Ribopatterns FTIRS PCA, PLS-DA [46] Pseudomonas spp. Species FTIRS HCA, ANN, PCA, SIMCA [45,49,53,86,92] Stenotrophomonas maltophilia Species FTIRS PCA, ANN [45,55] Ralstonia pickettii Species FTIRS ANN [45] Achromobacter spp Species FTIRS ANN [45] Yersinia spp.…”
Section: Bacteria Discrimination Level Infrared Technique Chemometricmentioning
confidence: 99%
See 2 more Smart Citations
“…Emphasis was also placed on the detection, discrimination, classification, and identification of bacteria -especially foodborne pathogens -such as Bacillus [19,20], Brucella [21], cyanobacteria [22], E. coli [23,24], lactobacilli [25], Listeria [26,27], Mycobacteria [28], Streptococcus [29], Salmonella [30,31], Staphylococcus [32,33], and Yersinia [34,35]. Also nosocomial pathogens, such as the members of the Burkholderia cepacia complex [36][37][38] possible warfare agents [39], and even fungi [40] were investigated. Thereby, samples in different conditions (liquid, suspended, powdered, or dehydrated) could be measured thanks to a variety of sampling methods and techniques available to record the spectra.…”
Section: Ir and Nir Absorption Spectroscopymentioning
confidence: 99%